Nature-positive agriculture for people and the planet: A qualitative analysis from Kenya - Kinuthia, Dickson; Oingo, Balentine; Bryan, Elizabeth; Davis, Kristin E.; Wallin, Elsa; Bukachi, Salome A. (International Food Policy Research Institute, 2024)
Agricultural intensification that prioritizes profits over people and the environment is increasingly recognized as harmful to people’s wellbeing and the sustainability and resilience of smallholder farming systems. Nature-based solutions are part of nature-positive eco-agrifood systems and are critical for restoring ecosystems and preventing further biodiversity loss and environmental degradation during a climate crisis. To support more widespread adoption of nature-based solutions, it is important to understand dynamics within local communities where these solutions will be applied. This includes deeper understanding of environmental challenges, institutional and governance arrangements, current farming practices, gender relations, and perceptions of nature-based solutions. This study draws on qualitative data on these topics collected from smallholder farmers and key informants in three counties of Kenya. The discussion centers on the potential for nature-based practices to place agricultural production systems on a more sustainable path.